Health promotion evaluation of specific sensitive nutrition interventions for stunting management at Bati Health Center, East Nusa Tenggara - Rupiasa, Welresna Juliatri Putri; Huriyati, Emy; Padmawati, Retna Siwi (BKM Public Health and Community Medicine, 2023)
Purpose: This study aims to determine the implementation of health promotion, including input, process, output, and outcome components in specific and sensitive nutrition interventions for handling stunting in the working area of Bati Health Center. Methods: This qualitative research uses the descriptive method with a purposive sampling technique so that the number of informants must meet the information adequacy requirements. Data analysis was carried out in a qualitative descriptive setting using a case study approach, which focused intensively on a particular object and studied it as a case. Case study data can be obtained from all parties concerned; in other words, data is collected from various sources. Results: In the input component, supporting health services and health promotion facilities, namely road access/transportation and electricity, still need to be improved. Another obstacle is the delay in providing incentives for health promotion human resources, which is related to delays in village funds. Conclusion: Cross-sectors need to support the implementation of health promotion in villages, including specific and sensitive nutrition interventions, to optimize the reduction of stunting rates in the working area of the Bati Health Center.